2016
DOI: 10.1136/jech-2016-207544
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the influence of social capital on depression in fragile families

Abstract: These results suggest that social and neighbourhood environments play an important role in mental health status. Intervention and policy initiatives that increase social capital may be viable for improving mental health among low-income urban, minority women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Such positive social connections are well known for supporting mental health (Kawachi & Berkman, 2001). Although higher levels of social cohesion may provide protection against poor mental health in high-poverty neighborhoods (Fone et al, 2014), reports of neighborhood social cohesion tend to be lower among mothers reporting higher levels of neighborhood social disorder (Franco, Pottick, & Huang, 2010;Wilmot & Dauner, 2017) and higher levels of parenting stress (Maguire-Jack & Wang, 2016) Parenting stress refers to processes and subsequent reactions that result from attempting to manage the challenges and burdens of parenthood (Deater-Deckard, 2008). Research using 2003-2004 National Survey of Children's Health data found at least one parent reporting high parenting stress in approximately 13% of households (Raphael, Zhang, Lius, & Giardino, 2010).…”
Section: Neighborhood Social Cohesion Parenting Stress and Mental Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Such positive social connections are well known for supporting mental health (Kawachi & Berkman, 2001). Although higher levels of social cohesion may provide protection against poor mental health in high-poverty neighborhoods (Fone et al, 2014), reports of neighborhood social cohesion tend to be lower among mothers reporting higher levels of neighborhood social disorder (Franco, Pottick, & Huang, 2010;Wilmot & Dauner, 2017) and higher levels of parenting stress (Maguire-Jack & Wang, 2016) Parenting stress refers to processes and subsequent reactions that result from attempting to manage the challenges and burdens of parenthood (Deater-Deckard, 2008). Research using 2003-2004 National Survey of Children's Health data found at least one parent reporting high parenting stress in approximately 13% of households (Raphael, Zhang, Lius, & Giardino, 2010).…”
Section: Neighborhood Social Cohesion Parenting Stress and Mental Hmentioning
confidence: 99%
“…Such positive social connections are well known for supporting mental health (Kawachi & Berkman, ). Although higher levels of social cohesion may provide protection against poor mental health in high‐poverty neighborhoods (Fone et al., ), reports of neighborhood social cohesion tend to be lower among mothers reporting higher levels of neighborhood social disorder (Franco, Pottick, & Huang, ; Wilmot & Dauner, ) and higher levels of parenting stress (Maguire‐Jack & Wang, )…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when a deprived area is considered, its social capital can be defined as a structural element of social relationships, which characterizes the groups and sub-groups of people who live there ( Villalonga-Olivesa 2018 ). Each individual's social capital is not simply a fixed characteristic but can be created or amplified ( Edwards 2010 ; Jones 2014 ; Wilmot 2017 ) with the contribution of the vulnerable individuals themselves. This can be achieved by specific social mechanisms, intentionally reproduced by individual, collective and institutional players.…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%
“…Some mechanisms hypothesized to link social capital at the individual level to health behaviors include diffusion of information and psychosocial processes that improve coping, self-esteem, and respect. Those mechanisms either have direct effects or buffer the effects of other determinants such as poverty, depression, and excessive alcohol use [18,[27][28][29]. Behavioral and psychological factors such as excessive alcohol use, depression, and self-reported HIV risk may also vary by gender and thus are important to examine as main variables rather than confounders.…”
Section: Introductionmentioning
confidence: 99%